2018
DOI: 10.1002/bmb.21169
|View full text |Cite
|
Sign up to set email alerts
|

Design and implementation of structural bioinformatics projects for biological sciences undergraduate students

Abstract: Contemporary biology is currently undergoing a revolution, driven by the availability of high‐throughput technologies and a wide variety of bioinformatics tools. However, bioinformatics education and practice is still in its infancy in most of the African continent. Consequently, concerted efforts have been made in recent years to incorporate bioinformatics modules into biological sciences curriculum of African Universities. Despite this, one aspect of bioinformatics that is yet to be incorporated is structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Governmental bodies and professional societies also began to take an interest and as early as 2003, discussions began to appear of how to do it all online, and for those with no prior experience . One interesting trend is to choose to emphasize structural bioinformatics, perhaps with an eye to continued demand for drug development "dockers" within the pharmaceutical industry. At the other end of the spectrum, Wightman and Hark emphasize the positive impact bioinformatics education has on the mathematical skills of biologists otherwise disinclined to numeracy.…”
Section: The Emergence Of Bioinformatics Curriculamentioning
confidence: 99%
See 1 more Smart Citation
“…Governmental bodies and professional societies also began to take an interest and as early as 2003, discussions began to appear of how to do it all online, and for those with no prior experience . One interesting trend is to choose to emphasize structural bioinformatics, perhaps with an eye to continued demand for drug development "dockers" within the pharmaceutical industry. At the other end of the spectrum, Wightman and Hark emphasize the positive impact bioinformatics education has on the mathematical skills of biologists otherwise disinclined to numeracy.…”
Section: The Emergence Of Bioinformatics Curriculamentioning
confidence: 99%
“…At Lancaster University, bioinformatics only began to appear in the undergraduate biology curriculum in academic year 2013–2014. In writing about the integration of bioinformatics into the undergraduate curriculum, I follow in the footsteps of various authors …”
Section: The Lancaster Undergraduate Bioinformatics Curriculummentioning
confidence: 99%
“…This paper not only contributes to the advancement of knowledge concerning laboratory practices in the pandemic era but also addresses the needs of educators in the field of genetics in the modern biology and digital education era. While various other papers have reported on the implementation of laboratory practices during the pandemic (Borish et al 2022;Delgado et al 2021; or the application of bioinformatics laboratory practices (O'Donnell et al 2014(O'Donnell et al , 2016Oke et al 2018), there is still no research that reports on the integration of bioinformatics activities into genetics laboratories, especially in Indonesia. Therefore, the aim of this research is to describe bioinformatics-based genetics laboratory practices conducted online at one of the private universities in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…In general, much bioinformatics instruction takes place at postgraduate level, e.g., MSc courses and doctoral training programmes [ 8 ], meaning that many life sciences students can earn their degrees with little or no bioinformatics training [ 5 , 9 ]. In the last few years, there has been a push to incorporate bioinformatics into undergraduate curricula [ 10 13 ]; however, a recent study found that one of the key barriers to this integration is a lack of student preparation [ 9 ].…”
Section: Introductionmentioning
confidence: 99%